Question
upstudy study bank question image url

wing exprertons (without using a calculator). rexpecise 26 - the following surds. (1) \( 25 i^{6} p^{10} \) 2. \( \sqrt[3]{8 x^{12} y^{15}} \) (B) \( 81 \times \sqrt{322^{3} y^{10}} \) 4. \( \sqrt{2 x^{3}} \times \sqrt{8 x^{3}} \) (5) \( (8) \sqrt{2} \cdot \sqrt{8} \) 6. \( \sqrt[6]{64 a^{6} b^{12} c^{18}} \) (0) \( \sqrt[x]{9 x^{10}+16 x^{10}} \) 8. \( \sqrt{\frac{27 x^{3} y^{5}}{12 x^{7} y^{3}}} \) (9) \( \mathrm{g} \sqrt{-} \times \sqrt{27 m} \) (10.) \( \sqrt{2 m^{3}} \times \sqrt{50 m x^{2}} \) (11) \( \frac{\sqrt{4 x^{1}}+\sqrt{4 x^{10}}}{5 x^{3}} \) 12. \( \sqrt[3]{3 x} \times \sqrt[3]{72 x^{5}} \)

Ask by Bryant Sherman. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. \( -25 p^{10} \) 2. \( 2 x^{4} y^{5} \) 3. \( 10368 y^{5} \sqrt{2} \) 4. \( 4 x^{3} \) 5. \( 32 \) 6. \( 2 a b^{2} c^{3} \) 7. \( 5 x^{5} \) 8. \( \frac{3 y}{2 x^{2}} \) 9. \( 3 g i \sqrt{3 m} \) 10. \( 10 m^{2} x \) 11. \( \frac{2(\sqrt{x} + x^{5})}{5 x^{3}} \) 12. \( 6 x^{2} \)

Solution

Let's simplify each of the given expressions step by step. ### 1. \( 25 i^{6} p^{10} \) First, we simplify \( i^{6} \): - \( i^{2} = -1 \) - \( i^{4} = 1 \) - \( i^{6} = i^{4} \cdot i^{2} = 1 \cdot -1 = -1 \) Now, substituting back: \[ 25 i^{6} p^{10} = 25 \cdot (-1) \cdot p^{10} = -25 p^{10} \] ### 2. \( \sqrt[3]{8 x^{12} y^{15}} \) We can break this down: \[ \sqrt[3]{8} = 2, \quad \sqrt[3]{x^{12}} = x^{4}, \quad \sqrt[3]{y^{15}} = y^{5} \] Thus, \[ \sqrt[3]{8 x^{12} y^{15}} = 2 x^{4} y^{5} \] ### 3. \( 81 \times \sqrt{32^{3} y^{10}} \) First, simplify \( \sqrt{32^{3}} \): \[ 32 = 2^{5} \implies 32^{3} = (2^{5})^{3} = 2^{15} \] So, \[ \sqrt{32^{3}} = \sqrt{2^{15}} = 2^{7.5} = 2^{7} \cdot \sqrt{2} = 128 \sqrt{2} \] Now, substituting back: \[ 81 \times \sqrt{32^{3} y^{10}} = 81 \times 128 \sqrt{2} \times y^{5} = 10368 y^{5} \sqrt{2} \] ### 4. \( \sqrt{2 x^{3}} \times \sqrt{8 x^{3}} \) Using the property of square roots: \[ \sqrt{2 x^{3}} \times \sqrt{8 x^{3}} = \sqrt{(2)(8)(x^{3})(x^{3})} = \sqrt{16 x^{6}} = 4 x^{3} \] ### 5. \( (8) \sqrt{2} \cdot \sqrt{8} \) First, simplify \( \sqrt{8} \): \[ \sqrt{8} = \sqrt{4 \cdot 2} = 2 \sqrt{2} \] Now substituting back: \[ (8) \sqrt{2} \cdot \sqrt{8} = 8 \sqrt{2} \cdot 2 \sqrt{2} = 16 \cdot 2 = 32 \] ### 6. \( \sqrt[6]{64 a^{6} b^{12} c^{18}} \) Breaking it down: \[ \sqrt[6]{64} = 2, \quad \sqrt[6]{a^{6}} = a, \quad \sqrt[6]{b^{12}} = b^{2}, \quad \sqrt[6]{c^{18}} = c^{3} \] Thus, \[ \sqrt[6]{64 a^{6} b^{12} c^{18}} = 2 a b^{2} c^{3} \] ### 7. \( \sqrt{x}{9 x^{10}+16 x^{10}} \) Combine the terms: \[ 9 x^{10} + 16 x^{10} = 25 x^{10} \] Now, \[ \sqrt{x}{25 x^{10}} = 5 x^{5} \] ### 8. \( \sqrt{\frac{27 x^{3} y^{5}}{12 x^{7} y^{3}}} \) Simplifying the fraction: \[ \frac{27}{12} = \frac{9}{4}, \quad \frac{x^{3}}{x^{7}} = \frac{1}{x^{4}}, \quad \frac{y^{5}}{y^{3}} = y^{2} \] Thus, \[ \sqrt{\frac{27 x^{3} y^{5}}{12 x^{7} y^{3}}} = \sqrt{\frac{9 y^{2}}{4 x^{4}}} = \frac{3 y}{2 x^{2}} \] ### 9. \( g \sqrt{-} \times \sqrt{27 m} \) Assuming \( g \sqrt{-1} = g i \): \[ g i \cdot \sqrt{27 m} = g i \cdot 3 \sqrt{3} \sqrt{m} = 3 g i \sqrt{3 m} \] ### 10. \( \sqrt{2 m^{3}} \times \sqrt{50 m x^{2}} \) Using the property of square roots: \[ \sqrt{2 m^{3}} \times \sqrt{50 m x^{2}} = \sqrt{(2)(50)(m^{3})(m)(x^{2})} = \sqrt{100 m^{4} x^{2}} = 10 m^{2} x \] ### 11. \( \frac{\sqrt{4 x^{1}}+\sqrt{4 x^{10}}}{5 x^{3}} \) Simplifying the square roots: \[ \sqrt{4 x^{1}} = 2 \sqrt{x}, \quad \sqrt{4 x^{10}} = 2 x^{5} \] Thus, \[ \frac{2 \sqrt{x} + 2 x^{5}}{5 x^{3}} = \frac{2(\sqrt{x} + x^{5})}{5 x^{3}} \] ### 12. \( \sqrt[3]{3 x} \times \sqrt[3]{72 x^{5}} \) Using the property of cube roots: \[ \sqrt[3]{3 x \cdot 72 x^{5}} = \sqrt[3]{216 x^{6}} = \sqrt[3]{216} \cdot \sqrt[3]{x^{6}} = 6 x^{2} \] ### Summary of Results 1. \( -25 p^{10} \) 2. \( 2 x^{4} y^{5} \) 3. \( 10368 y^{5} \sqrt{2} \) 4. \( 4 x^{3} \) 5. \( 32 \) 6. \( 2 a b^{2} c^{3} \) 7. \( 5 x^{5} \) 8. \( \frac{3 y}{2 x^{2}} \) 9. \( 3 g i \sqrt{3 m} \) 10. \( 10 m^{2} x \) 11

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

First, let's simplify the expression \( 25 i^{6} p^{10} \). Since \( i^2 = -1 \), we can find \( i^6 \) as follows: \( i^6 = (i^2)^3 = (-1)^3 = -1 \). Therefore, \( 25 i^{6} p^{10} = 25(-1)p^{10} = -25p^{10} \). Now, let's tackle the expression \( \sqrt[3]{8 x^{12} y^{15}} \). The cube root can be taken separately for each term: \( \sqrt[3]{8} = 2 \), \( \sqrt[3]{x^{12}} = x^4 \), and \( \sqrt[3]{y^{15}} = y^5 \). Combining these gives us \( 2x^4y^5 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy